PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI - Sulfaidah; Hindi, Alfiah Nurfadhilah AM; Amaliah, Ninah Wahyuni; Syam Pratomo, Ryan Humadani; Aswad, Sitti Hajar (Jurnal Pengabdian Kepada Masyarakat Patikala, 2023)
Community Service conducted training for teachers at SMA Cendrawasih Makassar and SMA Jaya Negera Makassar to create technology-based learning media. The method of implementing this Community Service activity (PkM) is a socialization of making technology-based learning media. The socialization was carried out in the form of training in making technology-based learning media for teachers of SMA Cendrawasih Makassar and SMA Jaya Negera Makassar. The success of this activity can be seen in the participants' responses during the activity. Indicators of the success of this PKM activity are as follows: (1) the positivity of the participants who participated in this training activity, (2) the active participation of the participants in each stage of this activity, (3) the enthusiasm of the participants in the training, and (4) the application of the results of this training in the learning process by the participants. Based on the results of observations that have been made by several servants, we state that this is indeed the case at the school. Partner problems that were found when we carried out visits to Internship III students who carried out learning in partner classes seemed that students were less motivated. Participants in this service activity totaled 19 participants who were teachers at the school. The school really welcomes this activity, considering the importance of learning media in supporting the learning process. This activity was also assisted by students of the Faculty of Education, Patompo University who were carrying out Internship III at SMA Cenderawasih Makassar and SMA Jaya Negara Makassar. SMA Cenderawasih Makassar and SMA Jaya Negara Makassar as stakeholders are very cooperative by being willing to serve as schools where PkM activities take place, where the teachers who are participants are very enthusiastic about participating in the activities. This PkM activity is very much needed by teachers considering the importance of learning media in supporting the learning process and in the end will increase student motivation and learning outcomes. The learning media carried out in the form of socialization and training in making technology-based learning media including Canva, Pear Deck, and Wordwall.